Virtual banking adoption: Challenges and opportunities from the perspectives of Jordanian customers - Shreim, Reem; Al-Kasasbeh, Basil (International Journal of Innovative Research and Scientific Studies, 2025)
Virtual banking represents a significant advancement in the banking sector, enabling banks to offer their services through digital channels such as online tools, applications, ATMs, phones, and internet communications, thereby eliminating the need for physical branch visits. However, the successful implementation of this virtual banking hinges on customers' perceptions and acceptance. Hence, this study focuses on the adoption of virtual banking in Jordan. This research examines the relationship between virtual banking and customers' intentions to use it in Jordan across four key dimensions: advantages, compatibility, simplicity, and trialability. Primary data were collected using a convenience sampling technique, with 130 participants responding to a structured survey. Subsequently, the collected data were analyzed using the SPSS tool (version 21) to extract both descriptive and inferential statistics. The results demonstrated a strong predictive capacity of independent variables in determining customer intention to use virtual banking. Furthermore, the study revealed significant positive correlations between advantages, compatibility, simplicity, trialability, and the intention to use virtual banking. Based on the findings, the study recommends that Jordanian banks should offer comprehensive banking services through digital platforms and incorporate various financial tools to cater to all customer needs. Ultimately, the adoption of virtual platforms possibly including ATMs should replace all in-person services provided by banks.